Chemical composition of the essential oil from aerial parts of Javanian Pimpinella pruatjan Molk. and its molecular phylogeny - Nurcahyanti, Agustina Dwi Retno; Sporer, Frank; Graf, Jürgen; Reichling, Jürgen; Wink, Michael (Diversity, 2016)
The species-rich and diverse genus Pimpinella is mainly distributed in Europe and Asia; a few species occur in Africa. Yet, the Javanian Pimpinella, P. pruatjan, which has been used as an aphrodisiac in Indonesian traditional medicine, was studied for the first time in the context of chemical composition, as well as phylogeny analysis and antimicrobial activity. We examined the chemical composition of the essential oil (EO) from aerial parts of P. pruatjan by gas liquid chromatography-mass spectrometry (GLC-MS). The main component of EO was (Z)-γ-bisabolene. Several oxygenated monoterpenes, oxygenated sesquiterpenes, and sesquiterpenes were also detected. The genetic relationship of Pimpinella pruatjan Molk. to other Pimpinella species was reconstructed using nucleotide sequences of the nuclear DNA marker ITS (Internal Transcribed Spacer). P. pruatjan clusters as a sister group to the African Pimpinella species. The EO did not exhibit an apparent antimicrobial activity.